Genetic diversity and genome-scale population structure of wild Indian major carp, Labeo catla (Hamilton, 1822), revealed by genotyping-by-sequencing - Sahoo, Bismay; Das, Gargee; Nandanpawar, Priyanka; Priyadarshini, Nirjharini; Sahoo, Lakshman; Meher, Prem Kumar; Udit, Uday Kumar; Sundaray, Jitendra Kumar; Das, Paramananda (Frontiers in Genetics, 2023)
Labeo catla (catla) is the second most commercially important and widely cultured Indian major carp (IMC) across the subcontinent as well as the neighbouring countries like Pakistan, Bangladesh, Nepal and Myanmar. In spite of the availability of substantial genomic resources in this important species, genome scale population structure is yet to be reported. In the present study, identification of genome wide single nucleotide polymorphisms (SNPs) and population genomics of catla were undertaken by re-sequencing of six catla populations of riverine origin from distinct geographical regions. DNA isolated from one hundred samples was used to perform Genotyping-by-sequencing (GBS). A published catla genome with 95% genome coverage was used as reference for mapping reads using BWA software. From a total of 472 million of paired-end (150 X 2 bp) raw reads generated in this study, we identified 10,485 high-quality polymorphic SNPs using the STACKS pipeline. Expected heterozygosity (He) across the populations ranged from 0.162 to 0.20, whereas observed heterozygosity (Ho) ranged between 0.053 and 0.06. The nucleotide diversity (π) was the lowest (0.168) in Ganga population. Within populations variation was found to be higher (95.32%) as compared to among populations (4.68%) variation. However, genetic differentiation was observed to be low to moderate, with Fst value ranging from 0.020 to 0.084, and the highest between Brahmani and Krishna population. Bayesian and multivariate techniques were used to further evaluate population structure and supposed ancestry in the studied populations using Structure and Discriminant analysis of principal components (DAPC), respectively. Both the analyses revealed the existence of two separate genomic clusters. The maximum number of private alleles was observed in the Ganga population. The findings of this study will help deeper understanding on the population structure and genetic diversity of wild populations of catla for future research in fish population genomics.